Attitudes and motivation of primary school learners in learning English as a second language / Sophia Metom - Metom, Sophia (2009)
It has been a great concern that English language learners at primary school level have difficulties in learning and acquiring the language. Researches have shown that attitudes and motivations play very important role in influencing English language learners. This case study intended to investigate the attitudes of the primary school learners towards learning English, to investigate how attitudes their learning of English, to identify the types of motivational factors that influence their learning and to what extend the motivational factors influence them. The samples of this study were 35 Year Six pupils of SK Sungai Maong Hilir, Kuching. The data were collected by means of checklists, semi-structured interviews and written diaries. The data were analyzed quantitatively and qualitatively, with descriptive analysis. The findings showed that 79.9% of these learners had positive attitudes and perceptions towards learning English. However, they were not confident to use English in their communication and writing. Their preference of using Bahasa Malaysia (BM) was undeniable. On the other hand, 20.1% of these learners need to be motivated, guided, persuaded and convinced to use the language.Nevertheless, their positive or negative attitudes greatly influence their learning of English. In addition to that, three (8.6%) of these learners whose first language was English were highly motivated, confident and comfortable in using the language. This study also revealed that these learners were greatly influenced by the extrinsic (63.4%) and intrinsic (79.6%) motivational factors in learning English. The prominent influential extrinsic factors are parents, family members, friends and teachers. On the other hand, the interest in learning English language, image as successfiil learners and the challenges of problem solving in learning the language are the intrinsic motivational factors